Perbandingan Tebal Perkerasan Lentur Metode Bina Marga 2017 dan Road Note 31 pada Jalan Tawang–Ngalang - Artha, Fransiska Dona; Novita, Dinda; Risdiyanto, Risdiyanto; Kresnanto, Nindyo Cahyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the comparison of flexible pavement thickness using the Bina Marga 2017 method and Road Note 31 edition 5 on the Tawang–Ngalang Segment IV road section, Gunungkidul Regency. This research adopts a quantitative approach using secondary data, including Average Daily Traffic (ADT) from the Prambanan–Piyungan road (2021) and Gading–Playen road (2020), as well as subgrade CBR data from 2022. The analysis was conducted by calculating traffic loading parameters, including ESA and CESA in the Bina Marga method and MESA in the Road Note 31 method, followed by determining pavement layer thickness based on each method. The results indicate that the Bina Marga 2017 method produces a pavement thickness of 54.5 cm, while the Road Note 31 method yields 54 cm, with a difference of 0.5 cm. This difference is influenced by variations in traffic load calculation approaches, where the Road Note 31 method requires detailed axle load data that is not yet comprehensively available in Indonesia.